Thermoluminescent response of differently doped lithium magnesium phosphate (LiMgPO4, LMP) crystals to protons, neutrons and alpha particles. (June 2018) - Gieszczyk, W.; Bilski, P.; Kłosowski, M.; Nowak, T.; Malinowski, L.
Abstract: Differently doped lithium magnesium phosphate crystals have been investigated with respect to their thermoluminescent properties. The LiMgPO4 crystals with Tb, B, Eu, Er, Tm, Y rare-earths elements were grown by the micro pulling down method. Different radiation qualities, such as protons of different energies, neutrons and alpha particles, have been used for samples irradiation. Thermoluminescent sensitivity to ionizing radiation, dose-response characteristics and relative thermoluminescence efficiency have been evaluated for all radiation qualities and compared for all analyzed crystal samples. It was found that the radio-sensitivity of the studied compound varies within several orders of magnitude depending on the applied doping ion and its concentration. The highest response was measured for the samples doped with thulium ions. In this case, the signal amplitude was about 3 times higher as compared to the standard LiF:Mg, Ti samples in the form of cold-pressed and sintered pellets. The dose-response of the studied LiMgPO4 crystals was found to be linear up to kGy range, regardless of the applied dopant and its concentration. An interesting behavior was observed in case of relative efficiency vs. linear energy transfer dependence. For protons of different energies the analyzed samples show a similar behavior as the reference LiF:Mg, Ti samples, showing a maximum efficiency evaluated for 20 MeV particles. The response of LiF-based samples for alpha particles decreases significantly to the value of around 0.08. The response of the analyzed lithium magnesium phosphate samples also decreases, but the decrease is not so significant in this case. This probably corresponds to the wide linear dose-response range and also indicates that the local signal saturation effects occur in this material in the range of much higher doses as compared to the reference LiF-based samples. Highlights: Differently doped lithium magnesium phosphate crystals were investigated. Thermoluminescent response to different radiation qualities has been compared. Relative TL efficiency of LMP to protons shows a similar trend as LiF-based samples. Response to alpha particles of LMP samples is higher as LiF-based reference samples. Doses at the level of kGy do not produce saturation effects in LMP material.